Behaviour of restrained steel beam at elevated temperature – parametric studies. (9th September 2019) - Allam, Ahmed; Nassif, Ayman; Nadjai, Ali
Abstract : Purpose: This paper aims to investigate computationally and analytically how different levels of restraint from surrounding structure, via catenary action in beams, affect the survival of steel framed structures in fire. This study focuses on examining the mid-span deflection and the tensile axial force of a non-composite heated steel beam at large deflection that is induced by the catenary action during exposure to fires. The study also considers the effect of the axial horizontal restraints, load-ratio, beam temperature gradient and the span/depth ratio. It was found that these factors influence the heated steel beam within steel construction and its catenary action at large deflection. The study suggests that this may help the beam to hang to the surrounding cold structure and delay the run-away deflection when the tensile axial force of the beam has been overcome. Design/methodology/approach: This paper is part one of the parametric study and discusses both the effect of the axial horizontal restraints and load-ratio on the heated steel-beam. Reliance on the prescriptive standard fire solutions may lead to an unpredicted behaviour of the structure members if the impact of potential real fires is not considered. Findings: Variation of the horizontal end-restraint level has a major effect on the behaviour of the beam at high deflection, and the loading on a beam at large displacement can be carried effectively by catenary behaviour. An increase of axial horizontal stiffness helps the catenary action to prevent run-away at lower deflections. The studies also investigated the influence of varying the load ratio on the behaviour of the heated beam at large deflection and how it affects the efficacy of the catenary action. The study suggests that care should be taken when selecting the load ratio to be used in the design. Originality/value: In a recent work, the large deflection behaviours of axially restrained corrugated web steel beam (CWSB) at elevated temperatures were investigated using a finite element method (Wang et al., 2014 ). Parameters that greatly affected behaviours of CWSB at elevated temperatures were the load ratio, the axial restraint stiffness ratio and the span–depth ratio. Other works included numerical studies on large deflection behaviours of restrained castellated steel beams in a fire where the impact of the catenary action is considered (Wang, 2002 ). The impact of the induced axial forces in the steel beam during cooling stage of a fire when the beam temperature decreases, if thermal shortening of the beam is restrained, large tensile forces may be induced in the beam (Wang, 2005 ;Allam et al., 2002 ). A performance-based approach is developed for assessing the fire resistance of restrained beams. The approach is based on equilibrium and compatibility principles, takes into consideration the influence of many factors, including fire scenario, end restraints, thermal gradient, load level and failure criteria, in evaluating fire resistance (Dwaikat and Kodur, 2011 ;Allam et al., 1998 ).